2018
DOI: 10.3390/ijerph15050977
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Information about Medicines Use among Parents of Pre-School Children in Serbia: Parental Pharmacotherapy Literacy Questionnaire (PTHL-SR)

Abstract: Parental health literacy plays an important role in children’s health. Experiences from pharmacy practice show that is necessary to check if parents understand instructions about use of medicines for children. This study aimed to assess pharmacotherapy literacy of parents of pre-school children and to examine association of parental pharmacotherapy literacy level with parent’s socio-demographic characteristics. The study was cross-sectional, conducted among parents of pre-school children (1–7 years of age), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 26 publications
(44 reference statements)
1
38
1
1
Order By: Relevance
“…Furthermore, patients' skills, e.g., how to interpret medication labels such as dosing and measurements was also emphasized in the development of medication literacy measure (Sauceda et al, 2012). In addition, King, Ubavić et al and Krajnović et al referred to four domains of pharmacotherapy literacy: knowledge, understanding for health information (written and spoken), numeracy, and access to medicinerelated information (King et al 2011;Ubavićet al, 2018a;Ubavićet al, 2018b;Krajnovic, 2019). The understanding for written or spoken information and numeracy were also emphasized in the concept of pharmacotherapy literacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients' skills, e.g., how to interpret medication labels such as dosing and measurements was also emphasized in the development of medication literacy measure (Sauceda et al, 2012). In addition, King, Ubavić et al and Krajnović et al referred to four domains of pharmacotherapy literacy: knowledge, understanding for health information (written and spoken), numeracy, and access to medicinerelated information (King et al 2011;Ubavićet al, 2018a;Ubavićet al, 2018b;Krajnovic, 2019). The understanding for written or spoken information and numeracy were also emphasized in the concept of pharmacotherapy literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge for medication specific for patients with certain kinds of disease was also incorporated in the concept of pharmacotherapy literacy and medication literacy (King et al, 2011;Sauceda et al, 2012;Ubavićet al, 2018a;Ubavićet al, 2018b;Krajnović et al, 2019). Therefore, knowledge for hypertension disease, treatment principal, and antihypertensives taking has been applied into operationalizing medication literacy for hypertensive patients in this present study.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, every third parent thinks that antipyretic should be given for every fever case [9]. Our study on pharmacotherapy literacy among parents of pre-school children in Serbia has shown that every fifth parent has difficulty understanding information that is given either in written or spoken form about the use of medicines [10]. Unintentional errors in the use of pediatric medicines made by parents can be very frequent and could be due to lack of knowledge and low levels of pharmacotherapy literacy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These errors are often related to liquid pediatric medicines, mainly antipyretics [14,15]. Socio-demographic characteristics, such as number of children, parental age, and level of education were reported to be factors that influenced the usage of antipyretic medicines [10].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient parental pharmacotherapy literacy was found to be an additional problem. Ubavic et al (5) found that more than half of parents (56.7 %) of pre-school children in Serbia were not able to properly understand the dosage regimen of over-the-counter (OTC) medicines on the package label and in patient information leaflets. Around the same percentage of parents in France do not properly prepare and reconstitute oral antibiotics, resulting in a risk of underdose or overdose (6).…”
mentioning
confidence: 99%